Platelet rich plasma versus corticosteroids for lateral epicondylitis: a meta-analysis of randomized clinical trials - Ralph Maroun; Mohammad Daher; Peter Boufadel; Ryan Lopez; Adam Z Khan; Joseph A. Abboud (Clinics in Shoulder and Elbow)
Background Lateral epicondylitis, colloquially known as tennis elbow, is a common cause of elbow pain and daily task disability. Caused by repetitive movement, it is typically a degenerative rather than inflammatory event and affects mostly middle-aged patients. Despite its good prognostic nature, its economic burden on the healthcare system encourages research on the efficacity of non-operative injection treatments. This article aims to compare the clinical effectiveness of platelet-rich plasma (PRP) and corticosteroid (CS) injections in managing lateral epicondylitis. Methods PubMed, Cochrane, and Google Scholar (pages 1–20) were searched up to March 2024. Only randomized controlled trials were included. The clinical outcomes evaluated were the visual analog scale (VAS) and Disabilities of the Arm, Shoulder, and Hand (DASH) score. Results Twenty-six randomized controlled trials with 1.877 patients were included in this meta-analysis. In terms of VAS scores, short-term results (<2 months) favored CS over PRP (P=0.03; mean difference [MD], 0.67; 95% CI, 0.05 to 1.28), whereas long-term results (>6 months) favored PRP (P<0.001; MD, –1.60; 95% CI, –2.01 to –1.20]). Intermediate-term results (2–6 months) showed no significant difference between injection treatments. In terms of DASH scores, short- and intermediate-term results showed no significant difference, whereas long-term results favored PRP (P<0.001; MD, –4.87; 95% CI, –7.69 to –2.06). Conclusions CS provides significantly better short-term pain relief, while PRP provides better long-term functional improvement and clinical long-term pain relief. However, future studies should focus on other injection protocols or addition of other non-invasive modalities. Level of evidence I.